Public knowledge, attitudes, and practices during the first wave of COVID-19 in Indonesia - Sinuraya, Rano K.; Wulandari, Chalisma; Amalia, Riezki; Puspitasari, Irma M. (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic became a global emergency, and it is vital to understand the knowledge, attitudes, and practices of populations regarding this disease to prevent its spread. Objective The study aimed to investigate the knowledge, attitudes, and practices of the Indonesian public toward COVID-19. Methods An observational study was conducted in Indonesia between November 2020 and January 2021. The study employed a validated questionnaire with 391 respondents to the survey. A comparative analysis was performed to assess the mean differences in respondents’ characteristics in terms of their knowledge, attitude, and practice scores. Furthermore, regression analysis was used to investigate those factors associated with the good practice of health protocols during the COVID-19 pandemic. Results The findings showed significant differences in the average knowledge scores across gender, geographical location, and educational attainment. Furthermore, significant differences in practices were identified in terms of gender and educational attainment. The findings of the study indicate that the participants demonstrated a significant awareness of COVID-19, as evidenced by their high mean knowledge score of 17.83 ± 1.74 out of a possible total score of 22 points. The results indicate that the respondents exhibited a positive attitude toward COVID-19 prevention measures, as evidenced by an attitude score of 26.95 ± 3.14 out of a possible total score of 30 points. Additionally, the mean score for good practice in health protocols aimed at reducing COVID-19 infection was found to be high (4.23 ± 0.96) at 5 points. This suggests that the study participants had already adopted effective measures to comply with the recommended health guidelines. The results of the regression analysis indicated that gender, level of education, and knowledge were statistically significant predictors for adherence to health protocols during the COVID-19 pandemic (p < 0.05). Conclusion The aforementioned results offer significant perspectives into the populace’s comprehension, disposition, and conduct regarding COVID-19 in Indonesia. These insights could potentially contribute to the formulation of efficacious measures aimed at curtailing transmission of the virus.